Event structure of problem situations - Viсtoria V. Dobrova; Helen V. Butina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the paper the notion of “situation” is analyzed in linguistic and psychological context. The review of approaches to the definition of situations is presented. Situation is defined as a complex of interconnected events taking place in exact place and time. The difference between situation and event is explained. The event structure of situation is suggested that includes number of its participants, their roles in the interaction in the situation. With the help of script description and frame analyses such situations as problem situations are described.